Encouraging Repeat Purchases: A Study of The Effects of Brand Image, Brand Trust, and Product Quality - Tresna, Muhamad Ikhsandi; Rohman, Fatchur (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This research investigates the influence of brand image, brand trust, and product quality on repurchase intention among Somethinc skincare users in Malang City. This study uses a quantitative approach, which seeks to identify relationships and explain the causes of measurable changes in social facts. Utilizing non-probability sampling and purposive sampling, 160 people with the minimum age of 18 years who have purchased Somethinc within the last six months and live in Malang City were selected as the respondents. The data quality was assured via classical assumption, validity, and reliability testing, and the data processing was conducted through multiple regression and descriptive analysis; all of which were performed in IBM SPSS Statistics 27. This study finds that brand image, brand trust, and product quality have a positive and significant impact on repurchase intention among Somethinc skincare users in Malang City.